Effects of supplemental amino acids and bile acid in a completely replaced fish meal by enzymatically hydrolysed soybean meal diet on growth performance, liver health and fillet quality of rainbow trout (Oncorhynchus mykiss). (18th March 2022) - Hang, Ying; Fu, You; Jin, Chenxu; Hua, Xueming
Abstract: In order to evaluate the supplemental effects of amino acids and bile acid to completely replace fish meal by enzymatically hydrolysed soybean meal diet for rainbow trout ( Oncorhynchus mykiss ), a 56‐day feeding trial was conducted with five diets, including 40% fish meal (FM) as a positive control diet, 45% enzymatically hydrolysed soybean meal without the fish meal (ESM) as a negative control diet, the addition of methionine (Met) and lysine (Lys) (0.76%) to the ESM diet (E+A), the addition of 0.02% bile acid to ESM diet (E+B) and the addition of Met and Lys (0.76%) and 0.02% bile acid to ESM diet (E+AB). The results showed that the ESM group reduced the growth performance but significantly alleviated the liver health problem, decreased lipid and saturated fatty acids (SFA) contents and increased protein content in fish muscle. The E+A group significantly improved growth performance, pepsin activity and fillet protein content, while the E+B group inhibited growth and protease activity but increased amylase activity, elevated SFA, monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) contents and improved lipid utilization. The E+AB group had superiority in enhancing liver health compared with E+A and E+B groups. This study suggested that supplemental amino acids and bile acid alone or in combination can be used according to practical feeding demand.